2019
DOI: 10.35120/kij34010175m
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Marketing With Special Description of Social Networks as a Marketing Tool

Abstract: The reasons that determine the behavior of food product consumers, but also of people in general, is one of the most complex issues in the marketing of companies and require extensive research, and the reason for this is the individuality and complexity of human. Knowing all the influencing factors grouped into determinants and discovering the correlations between them will lead to a wealth of information on the impacts and consumer behavior. Social platforms (networks) on the internet are very popular today, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to gender, we revealed that females are more aware of the antibacterial, antioxidant and enzymatic activity of honey. Research by Martinovski and Gulevska (2017) was focused on evaluating the consumer's knowledge about honey and its nutritional value. Based on the results, the relationship between respondents' knowledge of the health benefits of honey in their diet and familiarity with the nutritional qualities of honey is moderate (r=0,48).…”
Section: Figure 1 Preferences For Monofloral Honeymentioning
confidence: 99%
“…According to gender, we revealed that females are more aware of the antibacterial, antioxidant and enzymatic activity of honey. Research by Martinovski and Gulevska (2017) was focused on evaluating the consumer's knowledge about honey and its nutritional value. Based on the results, the relationship between respondents' knowledge of the health benefits of honey in their diet and familiarity with the nutritional qualities of honey is moderate (r=0,48).…”
Section: Figure 1 Preferences For Monofloral Honeymentioning
confidence: 99%